2019
DOI: 10.9734/ajaees/2019/v33i430186
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Urban Expansion on Agricultural Resources: A Case Study of Embu Town in Kenya

Abstract: Aim: To determine the effect of urban development on agricultural resources in peri-urban areas of Embu town. Study Design:  Descriptive survey design involving observational and survey methods. Place and Duration of Study: The study was carried out in three sub-locations lying within the peri-urban areas of Embu town, namely, Kamiu to the East, Njukiri to the West and Nthambo to the North of the town. The study was carried out from June to August 2018. Methodology: Purposive stratified sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Table 2 shows that the mean size of land allocated to banana production was 2 acres. The small farm sizes were attributed to land fragmentation resulting from the ever-swelling population growth in the study area (Murimi, Njeru, Gichimu & Ndirangu (2019). The results further showed that majority of the respondents engaged about 80 man-days per year in banana production.…”
Section: Characteristics Of Banana Production Among the Smallholder Farmersmentioning
confidence: 72%
“…Table 2 shows that the mean size of land allocated to banana production was 2 acres. The small farm sizes were attributed to land fragmentation resulting from the ever-swelling population growth in the study area (Murimi, Njeru, Gichimu & Ndirangu (2019). The results further showed that majority of the respondents engaged about 80 man-days per year in banana production.…”
Section: Characteristics Of Banana Production Among the Smallholder Farmersmentioning
confidence: 72%
“…Consequently, two sub-county schools within this sub-county were selected using voluntary sampling, ensuring adherence to the predetermined sample size. Being situated in a peri-urban area, the selected schools experience similar school challenges and experiences including inadequate infrastructure, limited access to resources, diverse student population with varying socioeconomic backgrounds, diverse learning environments, and insufficient funding [ [91] , [92] , [93] ]. One of these schools constituted the treatment group, where learners were instructed using constructive simulation, while the other school comprised the control group, employing the conventional teaching method.…”
Section: Methodsmentioning
confidence: 99%
“…Scale of farming due to limited land size was as much a problem especially in Ishiara and Karurumo where 90% of the farmers operated in less than 2 acres of land. This was attributed to by densely populated constituencies in Embu County (KNBS (Kenya National Bureau of Statistics), 2015) resulting to urbanization which has consequently led to pressure on agricultural land (Murimi, Njeru, Gichimu, & Ndirangu, 2019). According to Ndirangu (2017) declining size of the farm holdings in most high agricultural potential areas as a result of continuous land fragmentation is currently a major policy concern in Kenya.…”
Section: Socio-demographic Characteristics Of Respondentsmentioning
confidence: 99%